The Two Sides of Sensory–Cognitive Interactions: Effects of Age, Hearing Acuity, and Working Memory Span on Sentence Comprehension - DeCaro, Renee; Peelle, Jonathan E.; Grossman, Murray; Wingfield, Arthur (Frontiers in Psychology, 2016)
Reduced hearing acuity is among the most prevalent of chronic medical conditions among older adults. An experiment is reported in which comprehension of spoken sentences was tested for older adults with good hearing acuity or with a mild-to-moderate hearing loss, and young adults with age-normal hearing. Comprehension was measured by participants’ ability to determine of the agent of an action in sentences that expressed this relation with a syntactically less complex subject-relative construction or a syntactically more complex object-relative construction. Agency determination was further challenged by inserting a prepositional phrase into sentences between the person performing an action and the action being performed. As a control, prepositional phrases of equivalent length were also inserted into sentences in a non-disruptive position. Effects on sentence comprehension of age, hearing acuity, prepositional phrase placement and sound level of stimulus presentations appeared only for comprehension of sentences with the more syntactically complex object-relative structures. Working memory as tested by reading span scores accounted for a significant amount of the variance in comprehension accuracy. Once working memory capacity and hearing acuity were taken into account, chronological age among the older adults contributed no further variance to comprehension accuracy. Results are discussed in terms of the positive and negative effects of sensory-cognitive interactions in comprehension of spoken sentences and lend support to a framework in which domain-general executive resources, notably verbal working memory, play a role in both linguistic and perceptual processing.